(untitled) (Research, Society and Development, 2020)
The present study aimed to describe the knowledge of nurses who work in an Adult Intensive Care Unit about the control of nosocomial infection. Descriptive field research with a qualitative approach. Seven nurses were interviewed, using the semi-structured interview technique, the data analysis was based on Minayo’s operative proposal. All ethical considerations were respected in accordance with Resolution No. 466/2012 (Brasil, 2012), with the approval of the ULBRA Ethics Committee contained in Opinion No. 3.239.370. The results found were: nurses recognize the importance of hospital infection control, as well as the risk factors for hospitalized patients, in the context of the Adult Intensive Care Unit. Regarding the development of skills and practices to reduce infection rates, the active role of the Hospital Infection Service within the unit is highlighted, in addition to preventive measures and care, such as the correct washing of hands, the use of protective equipment individual care and care with contact isolation. However, it is difficult to guarantee the engagement of all health professionals who work in the unit to raise awareness of the adoption of such practices. The adoption of measures aimed at controlling nosocomial infection is prioritized in nurses’ daily practices. Continuing education elucidates several aspects of infection control that are not restricted to the hospital environment. Thus, preventive actions start even before hospitalization and can prevent unnecessary hospitalizations.